KESALAHAN PENERJEMAHAN DRAMA JEPANG ICHI RITTORU NO NAMIDA KARYA MASANORI MURAKAMI - Duwi Nugroho, Rahadiyan; Wahyu Andarwati, Titien; Zuliastutik, Hendri (Pusat Pengembangan Bahasa IAIN Tulungagung, 2020)
This study discusses the translation errors of the Indonesian subtitles from the Japanese drama Ichi Rittoru no Namida ?One Liter Tears? by Masanori Murakami, released at Fuji Terebi in 2005. There is no reference to similar study about the translation of oral dialogues of Japanese characters who were later translated into in Indonesian is of interest in this study. This study aims to identify the variety of Japanese drama Ichi Rittoru no Namida?s translation errors (subtitles). The formulation of the problem is examined with translation theory, types of translations and translation strategies. Furthermore, the data of this study are sentences or conversations in Japanese as the source language (SL) and Indonesian (subtitle) as the target language (TL) taken from episodes 1 to 6. The data are described using descriptive-qualitative methods. The results of this study are translation errors identified in diction choices, excessive use of words, grammatical errors, shifts in translation and errors due to cultural influences. Some examples of findings include the choice of diction like the word touzen translates to ?legitimate?, excessive use of words such as the word gomen ne to ?I am very sorry?, grammatical errors such as the phrase kondo no kusuri traced to ?the medicine he is taking?, the translation shift as in the noun phrase todoufuken ga shiteishita ishi no shindansho it becomes ?specified special health service? and errors due to cultural influences such as the yoroshiku expression becomes ?dependent on you?. Keywords: Ichi Rittoru no Namida, SL, TL, translation error